Hubungan Antara Pola Pemberian Makanan Pendamping Asi (Mp-Asi) Dengan Status Gizi Balita Usia 7-24 Bulan Di Wilayah Kerja Puskesmas Pucangsawit Kecamatan Jebres Kota Surakarta - SULISTYORINI, DWI, Dwi Sarbini, S.ST., M.Kes, Dyah Widowati, SKM (2015)
Introduction : Nutritional status is a state of the body as a result of the interaction of the balance of nutrients or energy intake and protein and nutrients other essential needs of the body, which are known by measurement of a variable and can be classified into the category of certain nutrients (nutritional status, better, less and bad).Forms of nutritional disorders are classified into two: overnutrition (excess nutrients) and under nutrition (malnutrition). Overnutrition is a state body due to consumption of certain nutrients exceed the needs of the body in a relatively long time. Undernutrition is the state of the body caused by nutrient intake daily that it can not meet the needs of the body. Objective: To determine the relationship between the pattern of complementary feeding (MP-ASI) with the nutritional status of children aged 7-24 months in Work Area Health Pucangsawit DistrictsJebres City Surakarta. Method: This research used in this study is observational with cross sectional approach. The samples are mothers who have children aged 7-24 months a number of 42 respondents. Retrieval of data by sequential sampling. Pattern of gift weaning obtained by filling a questionnaire that has been provided and the nutritional status of children is obtained by measuring anthropometry. Results : The results showed that the pattern of gift weaning influenced by nutritional status according amounted to 5.26% and is not suitable for 34.78%, while the nutritional status of children in category B/U is 21.42 % malnutrition children, 26.19% stunting, good nutrition 42.85%, and 9.52% more underweight children. Conclusions : There is a relationship between the pattern of complementary feeding (MP-ASI) with the nutritional status of children aged 7-24 months with a value of p = 0.016. Keywords : Giving Patterns complementary feeding, nutritional status. Literature : (24) 1999-2014.